2007
DOI: 10.1182/blood-2006-11-053769
|View full text |Cite
|
Sign up to set email alerts
|

DC-HIL is a negative regulator of T lymphocyte activation

Abstract: IntroductionT-cell activation is dependent on signals delivered by antigenpresenting cells (APCs) to the antigen (Ag)-specific T-cell receptor (TCR) and accessory receptors on T cells. 1 The principal stimulatory accessory signal is transmitted by B7-1 (CD80) or B7-2 (CD86) on APCs to the CD28 receptor on T cells. 2 Interestingly, engagement of the same B7-1 or B7-2 ligand to CTLA-4 (CD152) on T cells markedly attenuates T-cell responses. 3,4 The importance of CTLA-4 as an inhibitory regulator of T-cell activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
120
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 112 publications
(128 citation statements)
references
References 41 publications
7
120
0
1
Order By: Relevance
“…We also found DC-HIL to deliver a potent inhibitory signal to T cells, in an Ag-independent manner, by binding a heparin/heparan-like saccharide of syndecan-4 (SD-4) on activated T cells (19,20). These findings led us to hypothesize that DC-HIL binds microbial pathogens in a similar manner.…”
Section: /Cd8mentioning
confidence: 74%
See 1 more Smart Citation
“…We also found DC-HIL to deliver a potent inhibitory signal to T cells, in an Ag-independent manner, by binding a heparin/heparan-like saccharide of syndecan-4 (SD-4) on activated T cells (19,20). These findings led us to hypothesize that DC-HIL binds microbial pathogens in a similar manner.…”
Section: /Cd8mentioning
confidence: 74%
“…Fc-fused proteins (DC-HIL-Fc, SD-4-Fc, Dectin-2-Fc, and Fc alone) were produced in COS-1 cells and purified as described previously (15,19).…”
Section: Fc-fused Recombinant Proteinmentioning
confidence: 99%
“…Osteoactivin (DC-HIL) impairs APC function, which might be one explanation for the observed IL-10 effect. 12,34 To further analyze the underlying gene-expression regulatory mechanisms of our previous findings, we performed a semiquantitative reverse transcription-PCR (RT-PCR) analysis to detect mRNA expression of MyD88, IRAK1, TRAF6 and mTOR in APCs generated as above.…”
Section: Il-10 Inhibits Tlr-mediated Activation Of Apcsmentioning
confidence: 99%
“…These results show that pNK cell interacts with stromal cell, but not with pNK cell itself. It has been reported that Gpnmb binds to heparin heparan sulfate proteoglycan (12). In addition, one of the binding partner of Gpnmb is syndecan4 (SD4) on activated T cell which functions as a negative regulator on T cell activation, although SD4 on B cell did not bind to Gpnmb (12,13).…”
Section: Gpnmb Binds Ligand Of Stromal Cellsmentioning
confidence: 99%
“…It has been reported that Gpnmb binds to heparin heparan sulfate proteoglycan (12). In addition, one of the binding partner of Gpnmb is syndecan4 (SD4) on activated T cell which functions as a negative regulator on T cell activation, although SD4 on B cell did not bind to Gpnmb (12,13). Thus, we determined the expression of SD4 and other SD family in OP9 cells to determine a candidate which enables to bind Gpnmb on cell surface (Fig.…”
Section: Gpnmb Binds Ligand Of Stromal Cellsmentioning
confidence: 99%